Ruang Lingkup Manajemen Keuangan Scope Of Financial Management - Dian Sudiantini; Ananda Suryadinata; Andini Shinta Rahayu; Anisa Bunga Aprilia; Anisa Dewi Lestari (Institut Nalanda, 2023)
Effective financial management is an important factor in the success and sustainability of the company. One of the key aspects of financial management is managing company liquidity. This abstract aims to describe the importance of managing liquidity and its impact on the company's financial performance. The results of the analysis show that good liquidity management contributes positively to the company's financial performance. Companies that have a high liquidity ratio tend to have a better level of profitability and are able to generate stable growth. In addition, good liquidity management also provides benefits in facing external challenges, such as financial crises or market fluctuations. The company's financial managers need to find the right balance between sufficient liquidity to meet operational needs and profitable investments. In addition, this research can also contribute knowledge regarding best practices in financial management to academics and researchers in this field.